2012
DOI: 10.1186/1479-5868-9-91
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a healthy food supply intervention in a military setting: positive changes in cereal, fat and sugar containing foods

Abstract: BackgroundIn Finland, all men are liable to military service and a clear majority completes service. The increasing prevalence of obesity also among soldiers concerns conscripts’ food choices. Conscripts are served nutritionally planned regular main meals but individual choices take place in free-time eating. This study assesses the effects in conscripts’ eating habits in an intervention targeting the supply of healthy foods available in the military setting.MethodsParticipants were 604 18-21-year old male con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 34 publications
(53 reference statements)
0
49
0
3
Order By: Relevance
“…The levels of OB (BMI≥30 kg/m 2 ) were slightly lower in Switzerland than in the listed countries (5.8% vs. 8.1–8.5%). In Finland, the plateauing of the OWOB increase among conscripts appeared four years earlier (in 2005/2006) than when it was signalled in Switzerland [67], whereas the BMI values of Austrian conscripts showed no signs of stabilization between 2006 and 2010 [65]. However, because conscription procedures and age-at-conscription rules vary from country to country, in the absence of a comparative international study these figures should be treated with caution.…”
Section: Discussionmentioning
confidence: 90%
“…The levels of OB (BMI≥30 kg/m 2 ) were slightly lower in Switzerland than in the listed countries (5.8% vs. 8.1–8.5%). In Finland, the plateauing of the OWOB increase among conscripts appeared four years earlier (in 2005/2006) than when it was signalled in Switzerland [67], whereas the BMI values of Austrian conscripts showed no signs of stabilization between 2006 and 2010 [65]. However, because conscription procedures and age-at-conscription rules vary from country to country, in the absence of a comparative international study these figures should be treated with caution.…”
Section: Discussionmentioning
confidence: 90%
“…An intervention in a military setting focused on placement of healthy foods in the garrison refectories and soldier's home cafeterias, and similar placement of healthy foods in the hospital cafeteria may be beneficial. 14 In another study, customers of a medical center cafeteria reported higher frequency of visits to the cafeteria after implementation of a healthful options food station. 11 A comprehensive and complete assessment of the nutrition environment must include an evaluation of availability of healthy food choices and food placement.…”
Section: Methodsmentioning
confidence: 98%
“…Quanto aos fatores envolvidos ao adoecimento físico e mental de policiais do estado do Rio de Janeiro, pode-se citar o sobrepeso e a obesidade, que associados ao sedentarismo e às escolhas alimentares dos trabalhadores, influenciam negativamente na sua saúde 6,20,21 . Entre os principais problemas encontrados estão: dores no pescoço, na coluna, problemas de visão, dores de cabeça e enxaquecas.…”
Section: Selecionados: 19 Artigosunclassified
“…Também se constatou que os membros das corporações que apresentam lesões musculoesqueléticas permanentes apresentam maior sofrimento psíquico. Tornam-se necessárias mudanças nas dimensões individual, profissional e nos aspectos institucionais referentes às condições e à organização do trabalho e dos serviços de saúde 20,22 .…”
Section: Selecionados: 19 Artigosunclassified